(untitled) (Research, Society and Development, 2023)
The objective of the work presented below is to describe the epidemiological profile of cases of infant death up to 1 year of age in the State of Pará in 2019. For this purpose, a descriptive study was carried out with data from the Notifiable Diseases Information System (Sinan) referring to the year 2019; the initial search was carried out under the topic “Vital statistics” and subtopic “Mortality - since 1996 by ICD-10” with delimitation of notifications regarding infant mortality in the State of Pará. Data collection was then performed through "row/column" crossings, using the fields to verify the data "Lista Mort CID-10", "Sex", "Color/race", " Mother’s age", "Mother’s education", "Gestational duration", "Pregnancy type", "Delivery type", "Birth weight", "Age group 1". A total of 2,094 deaths of children under 1 year of age were verified in the State of Pará in 2019, resulting in an infant mortality rate of 15.13. Thus, it was observed that the rates for the 2019 period are above the national rates (12.38) and the rate for the North Region (15.12). In addition, the data found in DATASUS point out as a risk factor for infant mortality: male gender, indigenous child, teenage mother, mother with low education, premature birth, lowbirth weight and twin pregnancy. As an outcome, it was found that the state of Pará has rates higher than the Brazilian rates of infant mortality, which reaffirms the need for public policies aimed at the maternal and child population.